2002
DOI: 10.1016/s1087-1845(02)00036-1
|View full text |Cite
|
Sign up to set email alerts
|

δ-(l-α-Aminoadipyl)-l-cysteinyl-d-valine synthetase, that mediates the first committed step in penicillin biosynthesis, is a cytosolic enzyme

Abstract: Penicillin biosynthesis by Penicillium chrysogenum is a compartmentalized process. The first catalytic step is mediated by delta-(L-alpha-aminoadipyl)-L-cysteinyl-D-valine synthetase (ACV synthetase), a high molecular mass enzyme that condenses the amino acids L-alpha-aminoadipate, L-cysteine, and L-valine into the tripeptide ACV. ACV synthetase has previously been localized to the vacuole where it is thought to utilize amino acids from the vacuolar pools. We localized ACV synthetase by subcellular fractionati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 20 publications
0
35
0
1
Order By: Relevance
“…1). The first two enzymes, ACVS and IPNS, are both located in the cytosol (19,32). As the pH of the cytosol in filamentous fungi is between 6.5 and 7.0 (9, 31), these enzymes are in their optimal physiological surroundings.…”
mentioning
confidence: 99%
“…1). The first two enzymes, ACVS and IPNS, are both located in the cytosol (19,32). As the pH of the cytosol in filamentous fungi is between 6.5 and 7.0 (9, 31), these enzymes are in their optimal physiological surroundings.…”
mentioning
confidence: 99%
“…However, the biochemical properties of this enzyme, such as in vitro optimal pH 8.4 (which resulted to be above that of the vacuolar pH), cofactor requirement, and protease sensitivity indicated that this enzyme was a cytosolic enzyme. This fact was confi rmed by immunoelectron microscopy [ 39 ].…”
Section: Tripeptide Biosynthesismentioning
confidence: 70%
“…Figure 3.2 shows the chromosomal organization of both genes, which share a bidirectional promoter and are intron-free, suggesting that they were passed from prokaryotes to eukaryotes by horizontal gene transfer [ 19 ]. The corresponding gene products have a cytoplasmic localization, indicating that the fi rst two biosynthesis steps occur in the cytoplasm [ 20 ].…”
Section: Biosynthesis Pathwaymentioning
confidence: 99%